MENINGKATKAN BRANDING, PACKAGING, PRODUCT, PRICE, DAN TASTE SEBAGAI PELUANG BISNIS BAGI UMKM - Nursari, Ayu; Rahyono, Rahyono; Wuryanti, Lestari; Vani, Wulan Septio; Lestari, Tria; Putri, Fadillah Amanda; Hidayat, Syarief; Mungkas, Ihfa (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2023)
MSMEs are able to provide jobs, reduce the number of unemployed and become a means of introducing local products so that they can be known by all levels of society. MSMEs are here because they provide opportunities that are utilized by MSMEs in providing community needs, businesses that are currently viral and provide business opportunities, tastes, prices are affordable to the general public, there are consumers who become loyal customers, availability of raw materials that open up business opportunities, and etc. This study uses qualitative methods, taken from two types of data in this study, namely primary data and secondary data. The purpose of this research is to find out how to improve product packaging branding, price and taste as a business opportunity for MSME. Providing material increases branding on social media mentoring. Mentoring activities were carried out for MSME qummy kit4, after analysis it could be concluded that the main problems faced were branding and marketing, as well as the lack of use of social media. This activity was carried out with the aim of providing education to MSME qummy kit4 regarding branding and the use of social media in product marketing and increasing sales. By doing online marketing, you can expand your product marketing network, because it is easily accessible to anyone, anytime and anywhere.